(Human Resources Development Strategy in Improving Employee Performance at the Bitung City Regional Personnel and Human Resources Development Agency - Legi, Michael; Langkai, Jeane; Kairupan, Sisca B (Lembaga Penelitian dan Pendidikan Mandala, 2023)
The purpose of this study was to examine how human resource development strategies in improving employee performance at the staffing and human resource development agency of Bitung City. This research found that there is still low employee discipline in carrying out work. Based on the data obtained by the author, it is known that the level of employee discipline for the last 3 (three) years at the Bitung City Regional Civil Service and Human Resources Development Agency has not been optimal. The Main Performance Indicators (IKU) of the Bitung City Regional Human Resources Staffing and Development Agency in 2022, there are still 3 (three) indicators that have not reached the target. Increasing the career development of the apparatus has not been effective where based on the results of the study it is known that throughout 2023 the Bitung City Government has conducted several inauguration activities (promotions) for Echelon II, III and IV positions, but employees of the Regional Human Resources Staffing and Development Agency totaling 28 ASNs have not received a promotion. The method in this research is descriptive qualitative. The results of the study are descriptive or describe with the help of interview measuring instruments supported by observation and documentation